De Novo Drug Design of Potential Inhibitors of SARS-CoV-2 Papain-like Protease - Edgar Clyde R. Lopez (Medical Sciences Forum, 2023)
Here, potential inhibitors of the SARS-CoV-2 papain-like protease (PLpro) are reported. A drug molecule (PLpro-50), designed de novo using generative neural networks, interacts with PLpro via hydrogen bonding, forming a salt bridge, and π–π stacking, making it a promising drug against PLpro. PLpro-50 has an excellent ADMET profile with good absorbability, high clearance, and low toxicity. Molecular dynamics analysis revealed the stability of the receptor–ligand complex of PLpro-50 and PLpro. An organic retrosynthesis study showed the feasibility of PLpro-50 to be synthesized using low-cost starting materials. Further studies should be performed to determine whether the determined drug candidates are efficacious in treating COVID-19 infections.